The institutional nature of U.S. hegemony: post 9/11 - Kromah, Lamii Moivi (My University, 2009)
Abstract: A fragmented world of competing states is potentially very unstable. As rival states challenge each other militarily, the outcome will likely generate a very uneven distribution of power. For many observers, the political solidarity and economic prosperity in the post-second world war world would not have been as great without United States (US) leadership. The hegemonic project involves using political and economic advantages gained in a world war to restructure the operation of the world market and interstate system in the hegemon's own image. The United States took the lead in opening markets, protecting allies, and promoting the stability of the non-communist world. Because of this great accomplishment, many people worry about the waning of American global leadership and the seeming unwillingness or inability of other states to step into the role. This research report will aim to provide evidence U.S. Hegemony is nothing to fear because since the end of World War II (WWII). U.S. hegemony has developed a system of complex interdependence that has immensely benefited the core states and the periphery. The security community that was fostered under U.S. hegemony will be the major factor in reducing the chances of great power war and also increasing the chances of peaceful conflict resolution.